Inhibition of HER2 enriches for Jagged1-dependent breast cancer stem cells: role for membrane Jagged1 - Shah, Deep; Wyatt, Debra; Baker, Andrew; Simms, Patricia; Peiffer, Daniel S.; Fernandez, Michelle L.; Rakha, Emad A.; Green, Andrew R.; Filipovic, Aleksandra; Miele, Lucio; Osipo, Clodia (American Association for Cancer Research, 2018)
Purpose: Human Epidermal Growth Factor Receptor 2 (HER2) positive breast cancer is driven by cells possessing stem-like properties of self-renewal and differentiation, referred to as Cancer Stem Cells (CSCs). CSCs are implicated in radiotherapy, chemotherapy resistance, and tumor recurrence. Notch promotes breast CSCs survival and self-renewal, and overexpression of Notch1 and the Notch ligand Jagged1 predict poor outcome. Resistance to anti-HER2 therapy in HER2+ breast cancer requires Notch1, and that combination of trastuzumab and a Gamma Secretase Inhibitor (GSI) prevents tumor relapse in xenograft models. Experimental Design: The current study investigates mechanisms by which HER2 tyrosine kinase activity regulates Notch-dependent CSC survival and tumor initiation. Results: Lapatinib-mediated HER2 inhibition shifts the population of HER2+ breast cancer cells from low membrane Jagged1 expressing to higher levels, independent of sensitivity to anti-HER2 treatment within the bulk cell population. This increase in membrane Jagged1 is associated with higher Notch receptor expression, activation, and enrichment of CSCs in vitro and in vivo. Importantly, lapatinib treatment results in growth arrest and cell death of Jagged1 low-expressing cells while the Jagged1 high-expressing cells continue to cycle. High membrane Jagged1 protein expression predicts poor overall cumulative survival in women with HER2+ breast cancer. Conclusions: These results indicate that higher membrane Jagged1 expression may be used to either predict response to anti-HER2 therapy or for detection of Notch sensitive CSCs post therapy. Sequential blockade of HER2 followed by Jagged1 or Notch could be more effective than simultaneous blockade to prevent drug resistance and tumor progression.